Product market competition and the disclosure of supply chain information - Yue Chen; Xiaotong Yang; Chun Yuan; Bing Zhu (China Journal of Accounting Research, 2022)
We investigate how product market competition affects corporate voluntary disclosure decisions, specifically regarding supply-chain information. Our results, based on a sample of manufacturing companies listed in China from 2010 to 2016, show that companies in more competitive industries disclose less customer/supplier information. The main results stand through several robustness tests. Further analyses show that the negative relationship between product market competitiveness and supply-chain information disclosure is stronger when the disclosure contains more incremental information and when competitors are more capable of gaining competitive advantage using the disclosed information. Our study contributes to the understanding of both the relationship between product market competition and voluntary disclosure decisions and the regulation of information disclosure to build a transparent capital market.